The Novel N, N‐bis‐2‐Hydroxyethyl‐2‐Aminoethanesulfonic Acid–Gluconate–Polyethylene Glycol–Hypothermic Machine Perfusion Solution Improves Static Cold Storage and Reduces Ischemia/Reperfusion Injury in Rat Liver Transplant. Issue 9 (4th July 2019) - Carnevale, Matías E.; Lausada, Natalia; Juan de Paz, Leonardo; Stringa, Pablo; Machuca, Mariana; Rumbo, Martin; Guibert, Edgardo E.; Tiribelli, Claudio; Gondolesi, Gabriel E.; Rodriguez, Joaquin V.
Abstract : Organ transplantation is the treatment of choice against terminal and irreversible organ failure. Optimal preservation of the graft is crucial to counteract cold ischemia effects. As we developed an N, N ‐bis‐2‐hydroxyethyl‐2‐aminoethanesulfonic acid–gluconate–polyethylene glycol (BGP)–based solution (hypothermic machine perfusion [HMP]), we aimed to analyze the use of this solution on static cold storage (SCS) of rat livers for transplantation as compared with the histidine tryptophan ketoglutarate (HTK) preservation solution. Livers procured from adult male Sprague Dawley rats were preserved with BGP‐HMP or HTK solutions. Liver total water content and metabolites were measured during the SCS at 0°C for 24 hours. The function and viability of the preserved rat livers were first assessed ex vivo after rewarming (90 minutes at 37°C) and in vivo using the experimental model of reduced‐size heterotopic liver transplantation. After SCS, the water and glycogen content in both groups remained unchanged as well as the tissue glutathione concentration. In the ex vivo studies, livers preserved with the BGP‐HMP solution were hemodynamically more efficient and the O2 consumption rate was higher than in livers from the HTK group. Bile production and glycogen content after 90 minutes of normothermic reperfusion was diminished in both groups compared with the control group. Cellular integrity of the BGP‐HMP group was better, and the histological damage was reversible. In the in vivo model, HTK‐preserved livers showed a greater degree of histological injury and higher apoptosis compared with the BGP‐HMP group. In conclusion, our results suggest a better role of the BGP‐HMP solution compared with HTK in preventing ischemia/reperfusion injury in the rat liver model.